Existence of Hilfer fractional neutral stochastic differential systems with infinite delay - Sivasankar, S.; Udhayakumar, R.; Muthukumaran, V.; Gokul, G.; Al-Omari, S. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The goal of this study is to propose the existence of mild solutions to delay fractional neutral stochastic differential systems with almost sectorial operators involving the Hilfer fractional (HF) derivative in Hilbert space, which generalized the famous Riemann-Liouville fractional derivative. The main techniques rely on the basic principles and concepts from fractional calculus, semigroup theory, almost sectorial operators, stochastic analysis, and the M¨onch fixed point theorem via the measure of noncompactness (MNC). Particularly, the existence result of the equation is obtained under some weakly compactness conditions. An example is given at the end of this article to show the applications of the obtained abstract results.
Шексіз кешігуі бар бөлшек-нейтралды стохастикалық Хильфер дифференциалдық жүйелерінің болуы
Существование дробно-нейтральных стохастических дифференцивльных систем Хильфера с бесконечным запаздыванием
Keywords: Hilfer fractional evolution system; Neutral system; Measure of noncompactness; Fixed point theorem